Customer Retention: A Literature Review - Bhenu Artha; Inna Zahara; Bahri; Niken Permata Sari (Profesional Muda Cendekia Publishing, 2022)
Customer retention is vital for businesses with much research literature now available and in most cases, is regarded as an indicator of acquisition performance, but factors influencing it have rarely been studied in the serial acquirer context. Customer experience has drawn a great deal of attention from scholars and business practitioners in the past few decades. Successfully designing and providing customers with an optimal experience has become a central priority for marketing theory and practice. Customer experience plays a key role for firms in creating a sustainable competitive advantage and building good customer relationships The objective of this research is to determine the factors associated with customer retention. I presented a literature study using systematic literature review of relevant publications and as a result of this process, 19 articles are included and then examined the bibliographical references to check the validity of the inquiry and to avoid any potential omissions. I identify several variables that affect by customer retention.